Brandom vs. Hegel: The Relation of Normativity and Recognition to the True Infinite. Issue 2 (4th September 2015) - Turken, Alper
Abstract : Robert Brandom's neo-pragmatist interpretation of Hegel suggests that Hegel understands normative statuses, and therefore all conceptual commitments, as social achievements based on reciprocal recognition. This is expressed in the slogan 'For Hegel, all transcendental constitution is social institution.' 1 An important problem with this interpretation lies in its oversight that Hegel's concept of true infinite is presupposed and operative in Hegel's account of recognition in Phenomenology . This paper argues that Hegel's theory of recognition in the Phenomenology is based on his logical concepts and therefore cannot institute them.